Pitfalls of Echocardiographic Image Perception: How to Overcome Them? - Leitman, Marina; Tyomkin, Vladimir; Beeri, Ronen (Frontiers in Medicine, 2022)
In recent years, the significant development of echocardiography systems has led to a sharp improvement in echocardiographic images' quality. In parallel with this, computerized technologies are also going far forward, which today make it possible to ensure a high level of transmission, storage, and display of echocardiography studies. Despite this, many cardiologists are not familiar with modern computerized technologies' new possibilities and continue to use the old standards. That is why many echocardiography laboratories with the best echocardiography systems work following the old minimalist approach. In this paper, we will look at some of the most common mistakes that result from the improper transmission, storage, and demonstration of echocardiography studies, and describe possible ways to overcome these problems.